Comprehensive Functional Analysis of N-Linked Glycans on Ebola Virus GP1 - Nicholas J. Lennemann (American Society for Microbiology, 2014)
ABSTRACT Ebola virus (EBOV) entry requires the virion surface-associated glycoprotein (GP) that is composed of a trimer of heterodimers (GP1/GP2). The GP1 subunit contains two heavily glycosylated domains, the glycan cap and the mucin-like domain (MLD). The glycan cap contains only N-linked glycans, whereas the MLD contains both N- and O-linked glycans. Site-directed mutagenesis was performed on EBOV GP1 to systematically disrupt N-linked glycan sites to gain an understanding of their role in GP structure and function. All 15 N-glycosylation sites of EBOV GP1 could be removed without compromising the expression of GP. The loss of these 15 glycosylation sites significantly enhanced pseudovirion transduction in Vero cells, which correlated with an increase in protease sensitivity. Interestingly, exposing the receptor-binding domain (RBD) by removing the glycan shield did not allow interaction with the endosomal receptor, NPC1, indicating that the glycan cap/MLD domains mask RBD residues required for binding. The effects of the loss of GP1 N-linked glycans on Ca2+-dependent (C-type) lectin (CLEC)-dependent transduction were complex, and the effect was unique for each of the CLECs tested. Surprisingly, EBOV entry into murine peritoneal macrophages was independent of GP1 N-glycans, suggesting that CLEC-GP1 N-glycan interactions are not required for entry into this important primary cell. Finally, the removal of all GP1 N-glycans outside the MLD enhanced antiserum and antibody sensitivity. In total, our results provide evidence that the conserved N-linked glycans on the EBOV GP1 core protect GP from antibody neutralization despite the negative impact the glycans have on viral entry efficiency. IMPORTANCE Filovirus outbreaks occur sporadically throughout central Africa, causing high fatality rates among the general public and health care workers. These unpredictable hemorrhagic fever outbreaks are caused by multiple species of Ebola viruses, as well as Marburg virus. While filovirus vaccines and therapeutics are being developed, there are no licensed products. The sole viral envelope glycoprotein, which is a principal immunogenic target, contains a heavy shield of glycans surrounding the conserved receptor-binding domain. We find that disruption of this shield through targeted mutagenesis leads to an increase in cell entry, protease sensitivity, and antiserum/antibody sensitivity but is not sufficient to allow virion binding to the intracellular receptor NPC1. Therefore, our studies provide evidence that filoviruses maintain glycoprotein glycosylation to protect against proteases and antibody neutralization at the expense of efficient entry. Our results unveil interesting insights into the unique entry process of filoviruses and potential immune evasion tactics of the virus.